A targeted functional RNA interference screen uncovers glypican 5 as an entry factor for hepatitis B and D viruses. Issue 1 (6th October 2015) - Verrier, Eloi R.; Colpitts, Che C.; Bach, Charlotte; Heydmann, Laura; Weiss, Amélie; Renaud, Mickaël; Durand, Sarah C.; Habersetzer, François; Durantel, David; Abou‐Jaoudé, Georges; López Ledesma, Maria M.; Felmlee, Daniel J.; et al.
Abstract : Chronic hepatitis B and D infections are major causes of liver disease and hepatocellular carcinoma worldwide. Efficient therapeutic approaches for cure are absent. Sharing the same envelope proteins, hepatitis B virus and hepatitis delta virus use the sodium/taurocholate cotransporting polypeptide (a bile acid transporter) as a receptor to enter hepatocytes. However, the detailed mechanisms of the viral entry process are still poorly understood. Here, we established a high‐throughput infectious cell culture model enabling functional genomics of hepatitis delta virus entry and infection. Using a targeted RNA interference entry screen, we identified glypican 5 as a common host cell entry factor for hepatitis B and delta viruses. Conclusion : These findings advance our understanding of virus cell entry and open new avenues for curative therapies. As glypicans have been shown to play a role in the control of cell division and growth regulation, virus–glypican 5 interactions may also play a role in the pathogenesis of virus‐induced liver disease and cancer. (Hepatology 2016;63:35–48)